Highly differentiated thyroidal cancer: modern aspects of personalized tactics in the period after the Chernobyl disaster - B. B. Guda (Клінічна хірургія, 2020)
Highly differentiated thyroidal cancer: modern aspects of personalized tactics in the period after the Chernobyl disaster